Genuine Multinational Staffing Policy: Expectations And Realities - Zeira, Yoram; Harari, Ehud (Academy of Management Journal, 1977)
The article discusses a 1977 study on the staffing policy of U.S. multinational corporations. Results indicated that there are several sources of morale problems existing in multinational corporations of the dominant type. These included blocked promotions, transfer anxieties, income gaps, and unfamiliarity and adaptability difficulties. The research also indicates that the accumulation of variegated international experience is not essentially translated into managerial behavior compatible with environmental needs and headquarter's expectations.